Pengaruh Aspek Afektif terhadap Prestasi Belajar Pemrograman Web dan Perangkat Bergerak Studi Kasus Kelas X RPL SMK PGRI 3 Malang - Annisa Mutiara Fari; Admaja Dwi Herlambang; Satrio Hadi Wijaya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Curriculum-13 contains an assessment of affective attitudes that focuses on the feelings, interests, and talents of each student. Some examples of attitudes that students have are self-confidence, discipline, and responsibility. This study discusses the effect or impact of affective attitudes (confidence, discipline, and responsibility) on success in the learning process in Web and Mobile Programming subjects. Measurement of affective attitudes was measured using a questionnaire containing statements related to behavior in class. Measurement of learning achievement is taken from daily test scores for one semester. The population used is class X RPL SMK PGRI Malang with a total of 55 respondents. This study is classified as a quantitative study because the processed information is in the form of numbers. Using the comparative causal method in order to convey causal relationships that focus on cause and effect. The type of statistics used in this study is parametric statistics. Testing the data through the process of testing the validity and reliability. Meanwhile, data classification uses descriptive analysis. The results of the descriptive analysis on the affective aspects and student achievement showed that they were in the medium category. Proof of hypothesis based on multiple regression analysis by performing t test and f test. Statistical results show that self-confidence has an effect on learning achievement of Web and Mobile Programming by 8.80% in a negative direction. While the attitude of discipline has an effect of 29.00% in a positive direction and an attitude of responsibility has an effect of 11.20% in a positive direction.